The Role of artificial intelligence in designing antibody-based therapy for Covid-19 - Wahyu Hidayati; Radiana Dhewayani Antarianto (Indonesian Archives and Biomedical Sciences, 2021)
For several decades ago, passive immunization has already proven its ability to treat some diseases, especially pandemic diseases. On the contrary, after antibiotics discovery, the usage of passive immunization becomes neglected. Nowadays, we face a pandemic situation, COVID-19, which needs the possible treatment to save patients lives while medicines and vaccines are under development. By learning from history, passive immunization seems to be the best choice to save patient lives. As a kind of passive immunization, antibody-based therapy successfully treats diseases, including infectious diseases. Several antibody-based therapies are developed, as vast as the technology development, especially after the genetic codes announced. This article highlighted the influence of genomics tools, which helps researchers develop various platforms in developing monoclonal antibodies with high safety and efficiency in production and application.